Sunspot observations by Pehr Wargentin in Uppsala in 1747. Issue 9 (28th January 2019) - Arlt, R.
Abstract : This article reports on solar observations by Pehr Wargentin made in Uppsala in 1747. Drawings of the sun accompanied by textual annotations are preserved in the archives of the Royal Swedish Academy of Sciences. Numbers of sunspot groups, as well as sunspot numbers, were derived for March 1 to May 13, 1747 (Gregorian), the latter being approximations for some days as the exact number of spots and pores in large groups was not mentioned by Wargentin. Sunspot positions were also derived for the observing period, where reliable ones were obtained from right ascension and declination measurements by Wargentin and less accurate ones were measured in his drawings of the solar disk.